A channel for ion irradiation of materials at the accelerator “Sokol” - Glazunov, L.S.; Goncharov, A.V.; Zats, A.V.; Karpus’, S.G.; Kuz’menko, V.V.; Levenets, V.V.; Pistryak, V.M.; Sukhostavetz, V.I. (Вопросы атомной науки и техники, 2006)
At the accelerator “Sokol” a channel for ion irradiation of materials is constructed. The channel comprising a beamline system, a slit device, an electrostatic scanning system with power and control modules, and an irradiation chamber is placed behind the analyzing magnet. The main technical parameters of the channel are the following: ions used – H, He, N, Ar; ion energy – 0.2…2 MeV; ion beam current – 2 µA; target zone being irradiated – from 2 ×2 mm up to 40×40 mm; target holder temperature – 80…450 K. Irradiation channel tests are performed together with experiments on polyimide films irradiation with hydrogen ions with an energy of 400 keV.